Artificial Intelligence as a paradoxical Digital Disruptor in the Accounting Profession: An Empirical Study amongst Accountants - Anil Kumar Doshi, Harisai; Balasingam, Suresh; Arumugam, Dhamayanthi (International Journal of Psychosocial Rehabilitation, 2020)
The nature of Industrial Revolution 4.0 reveals the secret regarding the waves of change that are appearing at unprecedented breath and scale due to the increasing potency of digital innovation. This is the crystallization of disruption addressed as the waves of digital disruption, driven by rapidly developed and continuously innovated digital technologies, such as, Artificial Intelligence. Thus, Artificial Intelligence as a Digital Disruptor interrupts the status quo, just like a megatrend in the ecosystem, thereby impacting businesses, companies, industries and professions. One of the major professions in sight is the Accounting Profession – which is observed to be impacted at a ‘paradox’. This is the ‘double impacting potential’ of Artificial Intelligence as Digital Disruptor – ‘creating opportunities’ but ‘igniting threats’, simultaneously. This is when it can complement or replace the profession completely – leaving the longevity of profession questionable. Thus, it is at this point where the research dwells into investigating how Artificial Intelligence creates opportunities and ignites threats in the profession, through twelve variables. Then the research turns around and looks at the tech embracing ability of the accountants through six determinants, to investigate the level of positive and negative influence of Artificial Intelligence – thereby revealing the continuity status of the profession. In pursuance of carrying out this study, the researcher uses mixed methods to collect, present, analyze, and interpret data, in order to provide a complete understanding of the phenomenon studied by the research.